Association between vertebrobasilar artery calcification and artery-to-artery embolism in the posterior circulation - Huan Yang; Haoyu Lu; Chen Xue; Liangjie Lin; Cuiyan Wang; Ximing Wang; Guiwen Yang; Qingqing Yin; Bo Liu (Scientific Reports)
Abstract Our study aimed to explore the calcification patterns of culprit lesions associated with artery-to-artery embolism (AAE) infarction in patients with vertebrobasilar artery atherosclerosis, using vessel wall magnetic resonance imaging (VW-MRI) and computed tomography (CT). We retrospectively analyzed data from patients undergoing VW-MRI and CT scans at two institutions. Patients with ≥ 50% vertebrobasilar atherosclerotic stenosis were categorized based on their stroke mechanisms as AAE (+) and AAE (-). Calcification profiles of the culprit lesion, including the morphology, location, quantity, and VW-MRI characteristics were compared among stroke patients. Multivariate logistic regression model was used to evaluate the relationship between vertebrobasilar artery calcification characteristics and the presence of AAE (+). Among the 151 stroke patients included, 56 (37.09%) were classified as AAE (+), while 95 (62.91%) as AAE (-). Multivariate regression analysis revealed the odds ratio of AAE (+) was 2.69 and 2.15 for the presence and count of spotty calcification, 3.33 for intimal-predominant calcification, and 3.65 for multiple calcifications. Calcification characteristics observed at the culprit lesion were associated with posterior circulation infarction in patients exhibiting AAE infarction. Understanding the relationship between intracranial artery calcification and stroke mechanisms may help clinicians improve stroke prevention and treatment.